Influence Of Good Corporate Governance, Profitability And Firm Size To Firm Value - Cindy Oktafiani; Angela Dirman (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2023)
This study aims to analyze the effect of Good Corporate governance, Profitability, and Firm Size on Firm Value. The population in this study are CGPI Listings companies listed on the IDX (Indonesian Stock Exchange) in 2017-2021. The samples in this study amounted to 12 companies with 5 years of observation and the total sample size was 60 sample data. Sampling method is done by using purposive sampling method. The data analysis method used in this study is multiple linear analysis with the help of IBM SPSS 25 software. The results of this study indicate that good corporate governance and profitability have a positive and significant effect on firm values, while firm value has a negative and significant effect on firm value.